ADVANTAGES OF IN-OFFICE 3D PRINTING FOR MIDFACE FRACTURE RECONSTRUCTION USING TITANIUM MESH - Daniela Sulea; Florin Sava; Liliana Gheorghe; Otilia Boisteanu; Andrei Nicolau; Mihai Liviu Ciofu; Victor-Vlad Costan; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study The purpose of this study is to evaluate the benefits of 3D printing in the management of midface trauma, in cases in which titanium mesh was used for the reconstruction. Material and methods We performed a review of midface fracture cases in which stereolithic models were used during the preoperative planning for the pre-bending of the fixation plates and titanium meshes. We evaluated the characteristics of the case, the protocol of 3D printing, the details of titanium mesh reconstruction and the surgery outcomes. Results By performing the material shaping preoperatively the surgery duration was decreased. The complexity of the procedure was reduced, due to the detailed pre-operative planning using patient-specific 3D printed models. The pre-shaped plates and titanium mesh were useful guides to the correct fracture reduction. The titanium mesh allowed the reconstruction of comminuted areas of bone and preservation of multiple bone fragments. The postoperative outcomes were in accordance with the preoperative planning. The contours and dimensions of the midface were accurately restored, as well as the functions. Conclusions The implementation of 3D printing in the management of midface fractures has multiple advantages that justify the current use of this method in the setting of acute trauma.